Vascular endothelial growth factor +405G/C polymorphism as a predictor of diabetic retinopathy - Azza K. Amer; Nervana A. Khalaf; Safia H. Aboelmakarem; Mehry S. Elsobky; Mona R. Abdelrasoul; Amira A. Abdelazeem; Shahira R. Noweir; Safa Refaat; Leqaa A. Moemen; Soheir A. Mohammed; Mona A. Abdelhameed; Mohmoud M. Kenawy; et al. (Bulletin of the National Research Centre, 2020)
Abstract Background Diabetic retinopathy is a multistage event, and the most important of it is angiogenesis. The possible association between vascular endothelial growth factor (VEGF) +405G/C gene polymorphism and various diseases, in which angiogenesis might be critical in disease development, encourages many investigators to study its role in diabetic retinopathy (DR) development in diabetics. The aim of this work is to investigate +405G/C polymorphism of VEGF gene in Egyptian patients with type 1 diabetes mellitus (T1DM) and to assess its possible role as a predictor for the development and progress of diabetic retinopathy. A cross-sectional, observational study was undertaken in a sample of type I diabetic patients who attend diabetes polyclinic of RIO Hospital, Giza, Egypt, between October 2012 and December 2016 and who were willing to participate. Two hundred and sixty-six type 1 diabetic patients were studied (108 males and 158 females). All subjects were analyzed for VEGF +405G/C polymorphism by real-time PCR using TaqMan pre-designed single nucleotide polymorphism (SNP) genotyping assay. Results There were increased serum levels of VEGF in T1DM suffering from DR compared to those without. Also, there was increased +405 C/C of VEGF polymorphism and C allele frequency related to the severity of DR (non-proliferative retinopathy (NPR), proliferative diabetic retinopathy (PDR), and macular edema (ME)) and type C phenotype (ischemic) in T1DM suffering from DR. Conclusion Serum levels of VEGF and its +405G/C polymorphism could be used in the evaluation, development, and progression of DR.